Health Spending in Japan : Macro-Fiscal Implications and Reform Options - Nozaki, Masahiro (IMF Working Papers; Working Paper ;, 2014)
Health spending has risen rapidly in Japan. We find two-thirds of the spending increase over 1990-2011 resulted from ageing, and the rest from excess cost growth. The spending level will rise further: ageing alone will raise it by 3 1\2 percentage points of GDP over 2010-30, and excess cost growth at the rate observed over 1990-2011 will lead to an additional increase of 2-3 percentage points of GDP. This will require a sizable increase in government transfers. Japan can introduce micro- and macro-reforms to contain health spending, and financing options should be designed to enhance equity.